STRUKTUR DAN FUNGSI SOSIAL LEGENDA SETEMPAT SAMPURAGA DI DESA SIRAMBAS KECAMATAN PANYABUNGAN BARAT KABUPATEN MANDAILING NATAL - Nofrialdi, Wendi; WS, Hasanuddin; Nasution, Muhammad Ismail (Jurnal Bahasa dan Sastra, 2018)
This research had a purpose to describe Social Structure and Function of Legend of Sampuraga Story. The theory used by researchers in this research was folklore theory. The type of this research is qualitative research with description method which is explaining facts explicitly obtained from research object. To be able to describe the Social Structure and Function of the Legend of Sampuraga, this research is done by analyzing the data as an object with the following steps. (1) to describe the Structure of Folklore Legend of Sampuraga. (2) to describe the socio-function of the folklore of the Samapuraga legend. Structures are elements that build a ceruta, there are elements that are (1) characterizations, (2) style of language, (3) events and plot, (4) point of view, (5) background, and (6) theme and mandate. Furthermore, social function is a form of community belief to folklore they have and become a separate function in their social life. The social functions are (1) as a means of entertainment, (2) as a means of education (3) a means of social control, (4) social solidarity inauguration, and (5) group identity. Based on data analysis conducted, it can be concluded that there are only 5 elements in the Structure of Folklore Legend because the point of view is not found in the folklore Legend Sampuraga. All the social functions described above apply to the community of folklore owner Legend Sampuraga.Keywords: folklore, sampuraga, social function